Meiofauna Biodiversity and Ecology - Semprucci, Federica; Sandulli, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sedimentary habitats cover the vast majority of the ocean floor and constitute the largest ecosystem on Earth. These systems supply fundamental services to human beings, such as food production and nutrient recycling. It is well known that meiofauna are an abundant and ubiquitous component of sediments, even though their biodiversity and importance in marine ecosystem functioning remain to be fully investigated. In this book, the meiofaunal biodiversity trends in marine habitats worldwide are documented, along with the collection of empirical evidence on their role in ecosystem services, such as the production, consumption, and decomposition of organic matter, and energy transfer to higher and lower trophic levels. Meiofaunal activities, like feeding and bioturbation, induce changes in several physico-chemical and biological properties of sediments, and might increase the resilience of the benthic ecosystem processes that are essential for the supply of ecosystem goods and services required by humans. As a key component of marine habitats, the taxonomical and functional aspects of the meiofaunal community are also used for the ecological assessment of the sediments' quality status, providing important information on the anthropogenic impact of benthos.